(untitled) (Comprehensive Journal of Science, 2026)
This work was carried out at the Faculty of Veterinary Medicine and Agriculture, University of Zawia, during the period from April to June 2024, for 6 weeks. The study examined the effect of a mixture of aromatic medicinal plants (thyme, rosemary, and garlic) at different levels on the hematology and the immune system of local chicks of domestic chickens. The group fed 100 mg of thyme showed the highest significant increase in the bursa, followed by the group fed 100 mg of garlic, with increases of 1.11, 1.30, and 1.23, respectively. There was no significant effect on the thymus gland through the experimental treatments, as the highest percentage was recorded in the control group, 1.20 IgA levels showed the highest value in the treatment fed 100 mg of thyme (84.3), followed by the treatment fed 100 mg of rosemary, and then the treatment fed 100 mg of garlic. The logical values obtained in this study indicated that the mean IgM was significantly higher in the T2 and T3 control groups compared to the control group in chickens fed a basal diet supplemented with 1% garlic (p≤0.05). There was a significant increase in hemoglobin levels, with the 100 mg garlic treatment outperforming the other experimental treatments, registering 14.7. The group fed 100 mg of thyme showed the highest significant difference in red blood cell volume, followed by the group fed 100 mg of garlic (45.6% and 43.2%, respectively).